First Human Implantation of a Bioresorbable Polymer Scaffold for Acute Traumatic Spinal Cord Injury: A Clinical Pilot Study for Safety and Feasibility. Issue 2 (14th June 2016) - Theodore, Nicholas; Hlubek, Randall; Danielson, Jill; Neff, Kristin; Vaickus, Lou; Ulich, Thomas R.; Ropper, Alexander E.
Abstract: SUPPLEMENTAL DIGITAL CONTENT: Supplemental digital content is available for this article. Direct URL citations appear in the printed text and are provided in the HTML and PDF versions of this article on the journal's Web site (www.neurosurgery-online.com ). BACKGROUND AND IMPORTANCE: A porous bioresorbable polymer scaffold has previously been tested in preclinical animal models of spinal cord contusion injury to promote appositional healing, spare white matter, decrease posttraumatic cysts, and normalize intraparenchymal tissue pressure. This is the first report of its human implantation in a spinal cord injury patient during a pilot study testing the safety and feasibility of this technique (ClinicalTrials.gov Identifier: NCT02138110). CLINICAL PRESENTATION: A 25-year-old man had a T11-12 fracture dislocation sustained in a motocross accident that resulted in a T11 American Spinal Injury Association Impairment Scale (AIS) grade A traumatic spinal cord injury. He was treated with acute surgical decompression and spinal fixation with fusion, and enrolled in the spinal scaffold study. A 2 × 10 mm bioresorbable scaffold was placed in the spinal cord parenchyma at T12. The scaffold was implanted directly into the traumatic cavity within the spinal cord through a dorsal root entry zone myelotomy at the caudal extent of the contused area. By 3 months, his neurological examination improved to an L1 AIS grade C incomplete injury. At 6-month postoperative follow-up, there were no procedural complications or apparent safety issues related to the scaffold implantation. CONCLUSION: Although longer-term follow-up and investigation are required, this case demonstrates that a polymer scaffold can be safely implanted into an acutely contused spinal cord. This is the first human surgical implantation, and future outcomes of other patients in this clinical trial will better elucidate the safety and possible efficacy profile of the scaffold.